Resource Management System for of the Utility Sector at The Base Wireless Sensor Networks - Sliusar, A.; Khrustalova, S. (ХНУРЕ, 2022)
This article is devoted to the problem of monitoring water consumption. This topic was analyzed and proved its relevance for all industries and economy. Currently, the problem of implementing automated information technology in the process of monitoring water consumption is relevant and very important.
Keywords: water supply; pipeline; monitoring; flow meter